Innovation Is an Important Factor of University Development - Dehkanova Mahliyo Shuhrat qizi (Zien Journals, 2021)
The term “innovation” can be found everywhere in both translated and local literature. Many authors define concepts such as “innovation”, “innovation” and “invention”, although they have different meanings. The concept of “innovation” first appeared in the scientific study of culturology in the 19th century and literally meant the incorporation of some elements of one culture into another.
Keywords: Innovation; knowledge; commercialization; literature